Add-on effects of total glucosides of paeony on conventional therapies for psoriasis: a systematic review and meta-analysis of randomized controlled trials - Ziqing Li; Jie Lu; Kewen Guan; Haiwen Liang; Chuanjian Lu; Chuanjian Lu; Chuanjian Lu; Jingjie Yu (Frontiers in Pharmacology)
BackgroundPsoriasis is an inflammatory and recurrent dermatological disease that is associated with multiple comorbidities. Conventional psoriasis therapies such as acitretin capsule and narrow-band ultraviolet B radiation (NB-UVB) are prone to decreased efficacy and adverse events in long-term application. Total glucosides of paeony (TGP), a plant extract from Radix Paeoniae Alba, are commonly used in conjunction with conventional therapies for psoriasis. This study aims to elucidate the add-on effect of TGP on conventional therapies in the treatment of psoriasis.MethodsSeven databases were searched from their inception to March 2024. Randomized controlled trials (RCTs) using TGP in conjunction with conventional therapies for psoriasis were included. The Risk of Bias 2.0 (RoB 2.0) tool was used to assess bias risk, and data analysis was conducted using RevMan V.5.4. Evaluation outcomes mainly involved a 60% or greater reduction of Psoriasis Area and Severity Index score (PASI 60) and a 50% or greater reduction of Psoriasis Area and Severity Index score (PASI 50).ResultsThis meta-analysis ultimately included 36 RCTs with 3,140 participants. The findings indicated that TGP combined with conventional therapies were superior to conventional therapies used alone on PASI 60 (RR = 1.32, 95% CI: 1.25 to 1.39, P < 0.00001) and PASI 50 (RR = 1.44, 95% CI: 1.13 to 1.84, P = 0.004). Several types of conventional therapies were prone to PASI 60 response when combined with TGP than conventional therapies using alone, such as oral medication (RR = 1.40, 95% CI: 1.14, to 1.71, P = 0.001), topical medication (RR = 1.47, 95% CI: 1.24 to 1.74, P < 0.00001), and NB-UVB (RR = 1.29, 95% CI: 1.16 to 1.43, P < 0.00001). Furthermore, the results suggested that TGP might reduce the incidence of adverse events occurred by conventional therapies for psoriasis.ConclusionThis meta-analysis demonstrated the preliminary clinical evidence supporting the addition of TGP to conventional therapies in treating psoriasis. Owing to the limited methodological quality of the included studies, well-designed RCTs are required to further illustrate the add-on effect of TGP on conventional therapies for psoriasis.Systematic Review Registrationhttps://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=439904, identifier CRD42023439904.